Brand Image Matters: Understanding How Purchase Intention Mediates Mobile Card Buying Decisions - Setiawan, Andre; Wilis, Ratih Anggoro (Universitas Muhammadiyah Sorong, 2026)
The purpose of this research is to determine the influence of brand image on purchasing decisions of IM3 mobile phone cards, with purchase intention as a mediating. Research employed an explanatory quantitative approach. The sample size was determined based on the formula proposed by Hair et al., resulting in 108 respondents who are IM3 mobile phone card users in the Greater Jakarta area. Data processing was carried out through the Partial Least Square approach using the SmartPLS 3.0 application software to examine the effect among variables. The results indicated that brand image has a positive and significant influence on purchase intention, brand image has a positive and significant influence on purchase decision, and purchase intention has a positive and significant influence on purchase decision. Furthermore, brand image also has a positive and significant indirect effect on purchase decision through purchase intention as a mediating variable. From a practical standpoint, the outcomes have offered some managerial insights for Indosat Ooredoo. These insights relate to creating marketing plans that were more impactful for their IM3 products through improving the brand's perception and boosting the customer's desire to buy.